The Influence of Leadership Style on the Performance of Employees of PT Pantja Tunggal Kniting Mill Semarang - Purwaningrum, Dyah; Sutaat, Sutaat (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Leadership style is a process in which a person influences other people or a group in an effort to achieve certain predetermined goals. By applying the right leadership style, a leader can motivate his employees to work optimally, so that employee performance can be better. Leadership style is a model or strategy for leading an organization. This research aims to determine the influence of leadership style on the performance of employees of PT. Pantja Tunggal Knitting Mill Semarang. Good employee performance is expected to trigger work enthusiasm towards the Company's vision and mission. The research method used is quantitative research using a simple linear regression method. The sample in this study consisted of 50 respondents using the census method. Data collection uses a questionnaire and data processing uses the SPSS Satistics Version 24.0 analysis tool. Leadership styles have advantages and disadvantages, depending on how a leader maximizes all the potential strengths of an employee. A successful leadership style is a leadership style that is based on conscience, norms, ethics, freedom, giving trust, supervision, ready to accept criticism, constructive suggestions, firm and respecting creativity, innovation and motivation. This will have an impact on improving performance, increasing professional competence and competency. The leadership style played by PT Pantja Tunggal Knitting Mill Semarang has a significant impact on employee performance.